Апроксимація електростатичного потенціалу молекули точковими зарядами, що імітують її електронні пари - Nikolaienko, T.Yu.; Bulavin, L.A. (Publishing house "Academperiodika", 2023)
The electrostatic component used in the traditional force fields significantly impacts their accuracy in modelling the noncovalent interactions peculiar to biomolecular systems, including hydrogen bonding. In this contribution, we present a physical model for approximating the electrostatic potential of a molecule (MEP) based on the first-principle decomposition of its charge density distribution into the localized components. In contrast to conventional schemes, which typically use atom-centered charges to approximate MEP, the proposed approach locates such charges in the positions selected so as to mimic the anisotropy of the electron density distributions related to the electron pairs of atoms or covalent bonds. This peculiarity leads to a more accurate representation of the overall electrostatic potential, as verified by applying the proposed model to approximate the electrostatic component of the intermolecular interaction energy in 145 noncovalently bound molecular complexes from GMTKN55 database. This benchmark showed the root-mean-square difference between the true and approximated values of the electrostatic component of 2.7 kcal/mol, which is 2.2 times lower as compared to the traditional RESP charges method used as a baseline.